Sequence-specific DNA binding by glucocorticoid receptor "zinc finger peptides". - Archer, T K (1990)
Steroid hormone receptors can activate or repress transcription from responsive loci by binding to DNA. We have examined the mechanism of DNA binding by individually synthesizing the putative "zinc finger peptides" from the rat glucocorticoid receptor. Atomic absorption studies show that the peptides will bind zinc on an equimolar basis, and circular dichroism experiments demonstrate a significant alteration in secondary structure in the presence of zinc. The results from a series of experiments establish that metal ion is required for binding to DNA and that the amino-terminal zinc finger shows a significantly greater affinity for glucocorticoid response element-containing DNA over control DNA. These observations indicate that a single synthetic "zinc finger peptide" is able to bind to DNA in a sequence-specific manner.